PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING KURIKULUM 2013 UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI DI SMA NEGERI 3 BOYOLALI - -, Fatah Assidiq -; -, Sunarto -; -, Jonet Ariyanto Nugroho - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
The purpose of this study is to improve student learning outcomes through learning model Discovery Learning with the help of media on the subjects of Economics class X IIS 1 SMA Negeri 3 Boyolali. This research is a Classroom Action Research. The study was conducted in 2 cycles, each cycle consisting of planning, execution, observation, and reflection. The subjects of the study were students of class X IIS 1 SMA Negeri 3 Boyolali which amounted to 36 students. Techniques of data collection using observation, interviews, test results learning, questionnaire satisfaction and documentation. Data analysis using data reduction techniques, data presentation and drawing conclusions. Application of learning discovery learning model proved to improve learners' learning outcomes. Improved learning outcomes in both written test assessments and attitudinal assessments on the application of discovery learning model learning are more effective than conventional learning both on achievement, attitudes and retention. This is evident from the increase in the value of participants' learning outcomes at the time of application of cycle I with the percentage mastery of learning outcomes 73% with a grade point average of 77.33 so it can be seen that there is an increase in the average value of the class of 2.86 (average value pre-cycle class 74.47 and grade point average I 77.33) and completeness increased by 36.00% (at 37% pre cycle and 73% cycle I). While the learning outcome of cycle II, the average value of the class experienced an increase in the average grade value of 4.72 (grade point average of cycle 77.33 and the average value of cycle class II 82.05) and the completeness increased by 13% (73% in cycle I and 86% cycle II). The conclusion based on the research result is the application of learning model of Discovery Learning with the help of media can improve the learning result of the students' economic grade X IIS 1 SMA Negeri 3 Boyolali.